[BP.10.02] NOX4 DEFICIENCY LEADS TO HYPERTENSION AND VASCULAR-RENAL FIBROSIS WITH ENHANCED EFFECTS IN ANG II-DEPENDENT HYPERTENSION. (September 2017) - Lacchini, S.; Harvey, A.; Lopes, R.; Montezano, A.C.; Rios, F.; Schroder, K.; Brandes, R.P.; Touyz, R.M.
Abstract : Objective: Nox1, Nox2 and Nox4 play a role in cardiovascular and renal oxidative stress in Ang II-infused hypertensive mice. However, the role of Noxs in models of chronic hypertension, which recapitulate human hypertension, is unclear. We previously showed that Nox1 and Nox2 are not involved in chronic Ang II-dependent hypertension. Here we questioned the role of Nox4 by studying transgenic mice expressing human renin (LinA3) that were crossed with Nox4−/− mice. Design and method: Four genotypes were generated: wildtype (WT), LinA3, Nox4-deficient (Nox4), and LinA3/Nox4-deficient (LinA3/Nox4) (n = 7–13/group). Blood pressure was measured by tail cuff. Kidneys and aortas were collected to assess remodeling and tissue collagen deposition (in renal interstitium and in the aortic tunica media). Results: Blood pressure was significantly increased in LinA3, Nox4 and LinA3/Nox4 mice vs WT. This was associated with increased NADPH oxidase activity. All three experimental groups exhibited vascular and renal remodeling with evidence of increased fibrosis. Although LinA3 had increased aortic wall thickness (+31%), there was no significant change in collagen deposition vs WT. On the other hand, Nox4 mice, which presented a similar increase in wall thickness to LinA3 (+31%), had significant increase in collagen deposition (+140%, p < 0.05). In LinA3/Nox4 mice, collagen deposition (+185%, p < 0.05) was increased vs LinA3. Qualitative analysis under polarized light revealed increased immature and mature collagen fibers surrounding medial smooth muscle cells in LinA3, Nox4 and LinA3/Nox4 groups. In the kidney, interstitial collagen deposition was increased in all groups vs WT (LinA3: +68%, Nox4−/−: +96%, LinA3/Nox4−/−: +197%, p < 0.05). LinA3/Nox4 had greater renal fibrosis vs LinA3 mice. Conclusions: Our findings demonstrate that Nox4 deficiency in LinA3 mice does not reduce blood pressure or vascular and renal remodeling. Nox4 deficiency was associated with increased blood pressure and vascular-renal fibrosis, effects that were variably enhanced in LinA3/Nox4 mice. These results suggest that Nox4 may be cardiovascular-renal protective, which when downregulated leads to blood pressure elevation and vascular and renal injury, processes that may be amplified by Ang II-dependent hypertension.